2014
DOI: 10.1097/brs.0000000000000614
|View full text |Cite
|
Sign up to set email alerts
|

Does Preoperative T1 Slope Affect Radiological and Functional Outcomes After Cervical Laminoplasty?

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 13 publications
4
55
0
Order By: Relevance
“…12,23 Some cervical parameters, such as T1 slope, cervical regional kyphosis, and K-line, have been reported as important factors related to laminoplasty outcomes. 5,10,24 C2-7 SVA is a parameter worth considering because it can cause poor QOL and axial neck pain after laminoplasty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,23 Some cervical parameters, such as T1 slope, cervical regional kyphosis, and K-line, have been reported as important factors related to laminoplasty outcomes. 5,10,24 C2-7 SVA is a parameter worth considering because it can cause poor QOL and axial neck pain after laminoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…13 However, relatively few publications have defined normative values for cervical or thoracic sagittal balance, and even fewer have directly evaluated the influence of cervical segmental and regional balance on outcomes in cervical surgery. 47 Scheer et al provided a definition of the cervical sagittal vertical axis (C2-7 SVA) that refers to the distance between a plumb line dropped from the centroid of C2 (or dens) and the posterosuperior aspect of C7. 7 This parameter is expected to provide a measure of cervical regional balance.…”
Section: Introductionmentioning
confidence: 99%
“…[4] An estimated 31% of patients with ACP develop cervical spondylotic myelopathy (CSM). [5] The associated degenerative changes in the cervical spine can be accelerated by involuntary movements of the head and neck, and neural elements can be stimulated or compressed by dynamic instability [6] and a herniated cervical disc, [7] particularly in the presence of developmental spinal canal stenosis. [8] Torg–Pavlov ratio [9] values of 0.80 or less have been shown to predict developmental spinal canal stenosis.…”
Section: Introductionmentioning
confidence: 99%
“…The recent work by Kim et al specifically investigating postlaminoplasty cases reported that the preoperative higher T1 slope is a risk factor for developing kyphotic change after 2 years 8) . However, others reported that T1 slope does not affect a change in CL after ELAP 7,11) . At present, the preoperative factors that predict postoperative kyphosis have yet to be fully identified.…”
Section: Introductionmentioning
confidence: 93%